CRIMINAL SANCTIONS OF FINES AND REPLACEMENT MONEY IN CORRUPTION CRIMINAL ACTS FROM THE PERSPECTIVE OF LEGAL JUSTICE - Mustofa, Mustofa; Rodhiyah, Siti (UNISSULA Semarang, 2024)
Purpose of sanctionscriminal fines and compensation in corruption crimeslegal justice perspective. Research methods usedNormative juridical uses three research approaches: the statute approach, the conceptual approach, and the comparative approach.Results of the research on sanctionscriminal fines and compensation in corruption crimesdoes not provide legal justice and a deterrent effect for perpetrators of corruption, because the fine imposed can be replaced with imprisonment and the length of imprisonment does not correspond to the amount of state financial losses. The law is said to provide a sense of justice if it produces legitimate legal consequences and if the law achieves its goal of directing or changing human behavior into lawful behavior.